DIRECT DIGITAL CONTROL IN A COMPLEX OF SOFTWARE DESIGN OF DIGITAL CONTROL SYSTEMS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
This article provides the functionality of creating direct digital control devices in the computer-aided design of digital automatic control systems (CAD of digital ACS), in a complex of software design of digital control systems (SDSDC complex) for automated process control systems. Technical tools are defined by the international standard IEC 61131-1: 2003 (Part 1: General data). The possibility of implementing SDSDC complex in direct digital control, single-cycle and multi-cycle ladder diagrams, identification of objects of management and synthesis of digital controllers in comparison with the international standard IEC 61131-3: 2003 (Part 3: Programming Languages) are evaluated. Users’ productivity is estimated as well as the possibility of its separation between the users at different stages of the design of digital systems of automatic control is assessed.